El destino de los indígenas del Uruguay - Klein, Fernando (Nómadas. Critical Journal of Social and Juridical Sciences, 2007)
The article deals with the reconstruction of Uruguay indigenous past taking into consideration the critical review of historical documents and archaeological survivals. It focuses its attention in the Charrua etnia that, even was quite insignificant in demographical numbers, it left a deep track that can be still watched in the Uruguayan country. The indigenous heritage can be observed in their courage, the defense of their cultural values and in their passion for freedom. The confrontation between the Charrua and the Creole culture lasted three centuries, and it had a perdurable effect in their culture and in their own lives. The relationship that was established can be described as one of big tension and a latent huge violence. The fighting had a terrible end and unfortunately, including the unavoidable acculturation, in Uruguay was reaffirmed definitively that there were no place for aboriginal cultures.